ANALYSIS OF POTENTIAL DRUG INTERACTIONS IN PNEUMONIA PATIENTS AT GUNUNG JATI REGIONAL HOSPITAL INSTALLATIONS, CIREBON - Su'udiyah, Kamilina; Hidayati, Nur Rahmi; Setyaningsih, Indah; Rohadi, Didi; Supriyadi, Yadi (Universitas Muhammadiyah Magelang, 2024)
Pneumonia patients with complex diseases require a variety of drugs so the possibility of drug interactions also increases. This study aims to determine patient characteristics, potential drug interactions, severity, description of the type of drug and number of interacting drugs, as well as the relationship between patient characteristics and drug interactions. This type of research is a retrospective analytical descriptive study. The research sample was the medical records of patients diagnosed with pneumonia who met the inclusion criteria. Determination of drug interactions using the Medscape application. The analysis uses a correlation test to determine the relationship between the number of drugs and comorbidities with potential drug interactions. The characteristics of patients based on age are 46-65 years (36%), the majority of gender is male (52%), the number of drugs most frequently used is ≥ 5 types of drugs (94%), the predominant comorbidity is asthma (19.3%). The number of potential drug interactions occurred in 60 patients (67%) out of a total of 90 pneumonia patients. The highest level of severity of potential drug interactions was 55.2%. The type and number of drugs that interacted most were dexamethasone with omeperazole (13.2%). The results of the Chi Square correlation test obtained a significance value of 0.00 where the significance result was <0.05, so it was concluded that the number of drugs used and comorbidities with drug interactions was correlated with an R value of 0.477, which means the correlation between the number of drugs used and comorbidities has a moderate level of correlation.